2017
DOI: 10.1186/s40900-016-0054-7
|View full text |Cite
|
Sign up to set email alerts
|

Priority setting in research: user led mental health research

Abstract: Plain English summary Involving people in health research is increasingly recognised as being important to make sure that research is focused more on the needs of people who use health services. At present, ideas about what should be researched most often comes from researchers and/or health professionals like doctors and nurses rather than people with a lived experience of mental illness. In this study, we will talk with this group of people from across Wales to explore what they think research i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…Participant responses suggested that allies have to work within practical constraints, seizing opportunities by corralling resources when they can, while at the same time advocating for the positions at multiple levels and across a range of settings. The stigma associated with mental illness further impacts on the perceived credibility of consumer researchers (Ghisoni et al., ; Hipes, Lucas, Phelan, & White, ; Segal & Hayes, ). Allies, on the other hand, are seen as credible due to their positions, professional background and research track record (Happell & Scholz, ; Hutchison, ).…”
Section: Discussionmentioning
confidence: 99%
“…Participant responses suggested that allies have to work within practical constraints, seizing opportunities by corralling resources when they can, while at the same time advocating for the positions at multiple levels and across a range of settings. The stigma associated with mental illness further impacts on the perceived credibility of consumer researchers (Ghisoni et al., ; Hipes, Lucas, Phelan, & White, ; Segal & Hayes, ). Allies, on the other hand, are seen as credible due to their positions, professional background and research track record (Happell & Scholz, ; Hutchison, ).…”
Section: Discussionmentioning
confidence: 99%
“…Each table has a facilitator (trained by the lead facilitator prior to the event) as well as a note taker. The roles of the lead and table facilitators were critical, especially in providing clear explanations of the group goal, promoting purposeful interactions between group members and helping participants to feel at ease [56]. All participants signed an informed consent form prior to participating in the event and the project was reviewed and approved by the local university research ethics board.…”
Section: Nominal Group Techniquementioning
confidence: 99%
“…Consumer leadership of the research process has been purported and demonstrated to strengthen both the quality and translation of research and achieves the goal of inclusive research practice "nothing about us without us" [14,15]. Due to unique knowledge developed through lived experience of mental illness and recovery, consumer researchers focus on different areas and ask different research questions [16].…”
Section: Consumer-led Researchmentioning
confidence: 99%